Communes in America, 1975-2000 - Miller, Timothy (Syracuse University Press, 2019)
Preface: A century of American international communities -- The century winds down, and communities thrive -- Cohousing comes to America -- The ecovillage revolution -- The spiritual search I : Christian and Jewish communities -- The spiritual search II : other religious communities -- Communities on purpose -- Communities in the media spotlight : crisis and controversy -- Conclusion and afterword: Into the twenty-first century -- Appendix A: A reflection on 400 years of American communes : Does communal activity come in waves? If so, when have they occurred? -- Appendix B: American intentional communities, 1900-2000.